Improvement of abdominal laxity with combined use of calcium hydroxylapatite and radiofrequency microneedling - David di Sessa (Sociedade Brasileira de Dermatologia (SBD), 2024)
In clinical practice, not all patients seem to benefit from treatment with calcium hydroxyapatite, often due to the improper indication of this procedure for patients who may require an associated surgical approach. In this context, our objective was to describe a practical method for evaluating and selecting the ideal patient for a non-surgical approach to abdominal skin laxity, along with presenting clinical cases treated with the combined use of calcium hydroxylapatite (CaHA) and microneedling with radiofrequency.